Time of Admission to the PICU and Mortality*. Issue 10 (October 2017) - McCrory, Michael C.; Spaeder, Michael C.; Gower, Emily W.; Nakagawa, Thomas A.; Simpson, Sean L.; Coleman, Mary A.; Morris, Peter E.
Abstract : Objectives: To evaluate for any association between time of admission to the PICU and mortality. Design: Retrospective cohort study of admissions to PICUs in the Virtual Pediatric Systems (VPS, LLC, Los Angeles, CA) database from 2009 to 2014. Setting: One hundred and twenty-nine PICUs in the United States. Patients: Patients less than 18 years old admitted to participating PICUs; excluding those post cardiac bypass. Interventions: None. Measurements and Main Results: A total of 391, 779 admissions were included with an observed PICU mortality of 2.31%. Overall mortality was highest for patients admitted from 07:00 to 07:59 (3.32%) and lowest for patients admitted from 14:00 to 14:59 (1.99%). The highest mortality on weekdays occurred for admissions from 08:00 to 08:59 (3.30%) and on weekends for admissions from 09:00 to 09:59 (4.66%). In multivariable regression, admission during the morning 06:00–09:59 and midday 10:00–13:59 were independently associated with PICU death when compared with the afternoon time period 14:00–17:59 (morning odds ratio, 1.15; 95% CI, 1.04–1.26; p = 0.006 and midday odds ratio, 1.09; 95% CI; 1.01–1.18; p = 0.03). When separated into weekday versus weekend admissions, only morning admissions were associated with increased odds of death on weekdays (odds ratio, 1.13; 95% CI, 1.01–1.27; p = 0.03), whereas weekend admissions during the morning (odds ratio, 1.33; 95% CI, 1.14–1.55; p = 0.004), midday (odds ratio, 1.27; 95% CI, 1.11–1.45; p = 0.0006), and afternoon (odds ratio, 1.17; 95% CI, 1.03–1.32; p = 0.01) were associated with increased risk of death when compared with weekday afternoons. Conclusions: Admission to the PICU during the morning period from 06:00 to 09:59 on weekdays and admission throughout the day on weekends (06:00–17:59) were independently associated with PICU death as compared to admission during weekday afternoons. Potential contributing factors deserving further study include handoffs of care, rounds, delays related to resource availability, or unrecognized patient deterioration prior to transfer. Abstract : Supplemental Digital Content is available in the text.